Abnormal activity of corneal cold thermoreceptors underlies the unpleasant sensations in dry eye disease. Issue 2 (February 2016) - Kovács, Illés; Luna, Carolina; Quirce, Susana; Mizerska, Kamila; Callejo, Gerard; Riestra, Ana; Fernández-Sánchez, Laura; Meseguer, Victor M.; Cuenca, Nicolás; Merayo-Lloves, Jesús; Acosta, M. Carmen; Gasull, Xavier; et al.
Abstract : Abstract: Dry eye disease (DED) affects >10% of the population worldwide, and it provokes an unpleasant sensation of ocular dryness, whose underlying neural mechanisms remain unknown. Removal of the main lachrymal gland in guinea pigs caused long-term reduction of basal tearing accompanied by changes in the architecture and density of subbasal corneal nerves and epithelial terminals. After 4 weeks, ongoing impulse activity and responses to cooling of corneal cold thermoreceptor endings were enhanced. Menthol (200 μM) first excited and then inactivated this augmented spontaneous and cold-evoked activity. Comparatively, corneal polymodal nociceptors of tear-deficient eyes remained silent and exhibited only a mild sensitization to acidic stimulation, whereas mechanonociceptors were not affected. Dryness-induced changes in peripheral cold thermoreceptor responsiveness developed in parallel with a progressive excitability enhancement of corneal cold trigeminal ganglion neurons, primarily due to an increase of sodium currents and a decrease of potassium currents. In corneal polymodal nociceptor neurons, sodium currents were enhanced whereas potassium currents remain unaltered. In healthy humans, exposure of the eye surface to menthol vapors or to cold air currents evoked unpleasant sensations accompanied by increased blinking frequency that we attributed to cold thermoreceptor stimulation. Notably, stimulation with menthol reduced the ongoing background discomfort of patients with DED, conceivably due to use-dependent inactivation of cold thermoreceptors. Together, these data indicate that cold thermoreceptors contribute importantly to the detection and signaling of ocular surface wetness, and develop under chronic eye dryness conditions an injury-evoked neuropathic firing that seems to underlie the unpleasant sensations experienced by patients with DED. Abstract : Discomfort in dry eye is possibly caused by an augmented ongoing activity in corneal cold neurons secondary to dryness-induced alterations in sodium and potassium channel expression.